IMPROVING STUDENTS LEARNING OUTCOMES IN THE MATERIAL OF PLANE AREA THROUGH SMALL GROUP LEARNING METHOD AT CLASS V STUDENTS OF SDN 2 JAMBESARI - Dewi Lestari, Konka; Azmi, Ulil (Journal of Social Science, 2025)
Objective: This study aims to enhance the learning outcomes of fifth-grade students in mathematics, specifically on the topic of plane area, by implementing a small group learning method combined with peer tutoring to address gaps in student engagement and understanding. Method: The research employed Classroom Action Research (CAR) procedures, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The study involved 13 fifth-grade students from SDN 2 Jambesari, utilizing group discussions and peer tutoring to foster active participation and improve comprehension. Results: The findings revealed a significant improvement in students’ mathematics performance. In the first cycle, student completion reached 61.5%, which increased to 92% in the second cycle. Observational data indicated heightened student engagement and active participation during small group learning compared to traditional whole-class instruction. Novelty: This study demonstrates the effectiveness of integrating small group learning and peer tutoring to overcome student passivity and enhance mathematical comprehension, providing a replicable model for addressing learning disparities in elementary education.